An isolated bladder endometriosis misdiagnosed as a bladder tumor - Yassine Ayari; Hamza Boussaffa; Ahmed Sellami; Selim Zaghbib; Ben Rhouma Sami; Yassine Nouira (Urology Case Reports, 2020)
Urinary bladder endometriosis as a part of deep infiltrating pelvic endometriosis is well known, but isolated bladder involvement is very rare. A 36-year-old woman, who had two cesarean sections, was complaining of dysuria, frequency and burning micturition. MRI showed a tissular mass probably originating from the cervix and suggestive of a sarcoma. Cystoscopy identified a nodular bluish retro trigonal mass, which was completely resected. Histopathological examination was consistent with a bladder endometrioma. The patient had a conservative treatment based on estrogen-progesterone combination. After three months’ follow-up, ultrasound and cystoscopy were performed showing no signs of recurrence.